2005
DOI: 10.1124/mol.105.018911
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of Glutathione Transferase Zeta Causes Oxidative Stress and Activation of Antioxidant Response Pathways

Abstract: Glutathione S-transferase (GST) zeta (GSTZ1-1) plays a significant role in the catabolism of phenylalanine and tyrosine, and a deficiency of GSTZ1-1 results in the accumulation of maleylacetoacetate and its derivatives maleylacetone (MA) and succinylacetone. Induction of GST subunits was detected in the liver of Gstz1 Ϫ/Ϫ mice by Western blotting with specific antisera and high-performance liquid chromatography analysis of glutathione affinity column-purified proteins. The greatest induction was observed in me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
63
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(72 citation statements)
references
References 34 publications
5
63
1
Order By: Relevance
“…Significant differences in GSTT1 null allele frequencies were observed between Caucasian, Asian, African and African American populations (Lee et al, 2008). The prevalence of GSTT1 null allele in the present study ranges from 11% to 22%, which is almost similar to the frequencies reported in Caucasians (Blackburn et al, 2006;Johansson et al, 1998;Mannervik et al, 2005). Korean population showed higher frequency of (45.3%) of GSTT1 null allele compared with the white Americans (20.4%), African Americans (21.8%), Mexican-Americans (9.7%) (Hoglund et al, 2009;Marinkovic et al, 2008) and Turkish populations (10.8-28.3%) (Oke et al, 1998;Shchipanov et al, 2008;Sura et al, 2008).…”
Section: Discussionsupporting
confidence: 76%
“…Significant differences in GSTT1 null allele frequencies were observed between Caucasian, Asian, African and African American populations (Lee et al, 2008). The prevalence of GSTT1 null allele in the present study ranges from 11% to 22%, which is almost similar to the frequencies reported in Caucasians (Blackburn et al, 2006;Johansson et al, 1998;Mannervik et al, 2005). Korean population showed higher frequency of (45.3%) of GSTT1 null allele compared with the white Americans (20.4%), African Americans (21.8%), Mexican-Americans (9.7%) (Hoglund et al, 2009;Marinkovic et al, 2008) and Turkish populations (10.8-28.3%) (Oke et al, 1998;Shchipanov et al, 2008;Sura et al, 2008).…”
Section: Discussionsupporting
confidence: 76%
“…Human GSTZ1, which is identical to maleylacetoacetate isomerase, catalyses two distinct reactions: the biotransformation of a range of α-haloacids, including dichloroacetic acid, a drinking water contaminant, and the GSH-dependent isomerization of maleylacetoacetate to fumarylacetoacetate, the penultimate step in the phenylalanine-tyrosine −/− mice display the induction of some of the cytosolic GST isoenzymes, and the constitutive expression of genes that are regulated by antioxidantresponse elements (AREs) and that respond to oxidative stress via the Keap1/Nrf2 signaling pathway, which regulates the expression of numerous detoxifying and antioxidant genes (Lim et al 2004;Lee and Johnson 2004). All of these findings support the view that the lack of GSTZ1 may induce oxidative stress (Blackburn et al 2006). The antioxidant role of GSTs is well known and derives essentially from their ability to regulate the concentration of GSH, the most powerful cellular antioxidant, in different cellular compartments including mitochondria, the principal source and target of ROS.…”
Section: Discussionsupporting
confidence: 73%
“…Induction of GST subunits was deleted in the liver of Gstz1 -/ -mice. The greatest induction was observed in members of mu class, especially Gstm1 (Lim et al, 2004;Blackburn et al, 2006). Based on published studies, at least some of the genetic polymorphisms are significantly associated with multifactorial traits only among specific ethnic groups (Hung et al, 2005;Kiyohara et al, 2006;Saadat, 2006;Saadat and Ansari-Lari, 2009).…”
Section: Resultsmentioning
confidence: 93%
“…In mice and human, the GSTz are expressed in many tissues at a low level (Blackburn et al, 2006). In mice, Gstz1 deficiency resulted in the generation of a constant level of oxidative stress (Blackburn et al, 2006). Several GSTZ1 variant sequences have been identified in humans (Blackburn et al, 2000;Fang et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation